What really hampers taxonomy and conservation? A riposte to Garnett and Christidis (2017) - Raposo, Marcos A.; Stopiglia, Renata; Brito, Guilherme Renzo R.; Bockmann, Flávio A.; Kirwan, Guy M.; Gayon, Jean; Dubois, Alain (Zootaxa, 2017)
Responding to purported taxonomic anarchy, in an article published in the widely read journal Nature, Garnett & Christidis (2017) [hereafter GC] opined on the need for “standardized global species lists”, at the behest of conservationists, and proposed the construction of a judicial committee to “restrict … freedom of taxonomic action” and promote taxonomic stability. Here we reflect on this perspective and contest that the view of GC conflicts with some basic and indisputable principles underpinning the philosophy of science, most notably: it must be free. They appear to believe that taxonomic revisions should be based on political, economic and conservation concerns, and they treat species as fixed real entities, instead of refutable scientific hypotheses. In addition to such theoretical misconceptions, GC did not consider important practical aspects of what they term taxonomic anarchy, most significantly the participation of conservationists as authors of taxonomic works, and the importance of alternative management units, a well-established discussion in conservation biology.